2012
DOI: 10.1016/j.bpj.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

PIP3 Waves and PTEN Dynamics in the Emergence of Cell Polarity

Abstract: In a motile eukaryotic cell, front protrusion and tail retraction are superimposed on each other. To single out mechanisms that result in front to tail or in tail to front transition, we separated the two processes in time using cells that oscillate between a full front and a full tail state. State transitions were visualized by total internal reflection fluorescence microscopy using as a front marker PIP3 (phosphatidylinositol [3,4,5] tris-phosphate), and as a tail marker the tumor-suppressor PTEN (phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 35 publications
7
75
0
Order By: Relevance
“…1). The average velocity of 0.11 mm6s 21 for the propagation of PIP3 bands in electrofused cells is similar to that in normal-sized cells, where an average of 0.14 mm6s 21 was found (Gerisch et al, 2012). In the cell shown in Fig.…”
Section: Wave Dynamics In Giant Cells As Compared To Those Of Normal supporting
confidence: 78%
See 3 more Smart Citations
“…1). The average velocity of 0.11 mm6s 21 for the propagation of PIP3 bands in electrofused cells is similar to that in normal-sized cells, where an average of 0.14 mm6s 21 was found (Gerisch et al, 2012). In the cell shown in Fig.…”
Section: Wave Dynamics In Giant Cells As Compared To Those Of Normal supporting
confidence: 78%
“…We produced these cells by electric-pulse-induced cell fusion or by myosin II knockout in order to investigate pattern dynamics not limited by the narrow borders of normal-sized cells, which have been studied previously (Gerisch et al, 2012). As with the wave patterns in normal cells, those in giant cells are generated spontaneously.…”
Section: Self-organization Of Wave Patterns In Giant Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2D). A recent study (24) suggested PTEN depletion proceeds a few seconds ahead of PIP3 accumulation. These events appear almost simultaneously in the time resolution (10-s interval) of the present analysis.…”
mentioning
confidence: 99%